Respiratory syncytial virus-associated hospitalizations among children: an Italian retrospective observational study - Francesca Fortunato; Angelo Campanozzi; Gianfranco Maffei; Fabio Arena; Valeria Delli Carri; Tiziana Rollo; Pier Luigi Lopalco; Domenico Martinelli (BMC, 2024)
Abstract Background Respiratory syncytial virus (RSV), a single-stranded RNA virus, is a leading cause of hospitalization in infants, especially ≤ 2 months of life. In the light new immunization strategies adoption, we described epidemiological and clinical characteristics of RSV-associated hospitalizations in pediatric and neonatal intensive care units of the Policlinico Foggia Hospital, Apulia Region, Italy. Methods Hospitalized children with a laboratory-confirmed RSV infection from 2011 to 2023 were retrospectively evaluated. Clinical information was collected from Hospital Discharge Registry in the period 2011-2020. The proportion of the hospitalization for acute respiratory infections (ARIs) associated to RSV was calculated and the hospitalization cost was analyzed by using the diagnosis-related group reimbursement rate. The anticipated impact of immunization either with monoclonal antibodies or maternal immunization on the number of hospitalizations was estimated. All analyses and quality assessment were performed using STATA/SE15.0. Results A total of 1,005 RSV-cases were included in the study, of which 86.3% occurred between December-March. In the period 2011-2020, 832 RSV-cases were matched with the corresponding hospital admissions; 75.2% were aged < 1 year (49.6% 0-2 months). Bronchiolitis was the most frequent admission diagnosis occurring in 63.3% of patients; 25% of children were affected by a very severe RSV-disease. Younger age ≤ 2 months (OR:14.8, 95%CI:8.30-26.31, p = 0.000), higher length-of-hospital-stay (OR:1.01, 95%CI:1.0-1.02, p = 0.030) and history of prematurity (OR:4.4, 95%CI:1.57-12.11, p = 0.005) were associated with a higher disease severity. RSV caused 48.9% of ARIs among children < 1 year. The mean cost of an RSV-associated hospitalization was 3,036 euros/year, with the higher cost in the 0-2 months age group (4,225 euros/year). Immunization programs with nirsevimab could prevent 51.4 RSV hospitalizations/year and 18.1 very severe RSV disease/year in infants < 1 year of age. RSV vaccine could prevent 46.1 of hospitalizations/year caused by RSV within 180 days after birth. Conclusions Our study contributes to outlining the baseline profile of RSV-associated hospitalizations among Italian children by providing epidemiological/clinical/economic estimates. While awaiting new recommendations on immunization, healthcare-workers should persist in implementing public health measures and appropriate case management to control RSV seasonal epidemics. Strengthened laboratory RSV surveillance is needed to inform the implementation of the new immunization strategies.